A review of the chemical composition and biological activities of Callistemon lanceolatus (Sm.) Sweet - Kandhasamy Sowndhararajan, Ponnuvel Deepa, Songmun Kim (Journal of Applied Pharmaceutical Science, 2021)
The genus Callistemon belongs to the family Myrtaceae that comprises approximately 50 shrub species. These species are mainly found in the east and southeast of Australia. Among them, Callistemon lanceolatus (Sm.) Sweet (common name: lemon bottlebrush) is an important medicinal plant and is traditionally used to treat various disorders. C. lanceolatus is widely distributed in tropical and subtropical regions. This plant contains a wide variety of chemical components such as triterpenoids, flavonoids, fatty acids, and phenolic compounds. In the present review, the chemical composition and biological activities of C. lanceolatus were summarized. In this regard, a literature search was carried out to retrieve information concerning the chemical composition and biological activities of C. lanceolatus from PubMed, Science Direct, Taylor and Francis, BMC, Wiley, Springer, ACS, Google Scholar, and other literature databases. The isolated compounds and extracts of C. lanceolatus were reported for a variety of biological properties, including antimicrobial, antioxidant, anti-inflammatory, antidiabetic, antiproliferative, and insecticidal activities. In this review, we attempt to combine the literature regarding phytochemical composition and biological activities of C. lanceolatus.
Keywords: Callistemon lanceolatus, lemon bottlebrush, biological activity, antimicrobial, essential oil